2015 IEEE Symposium on Security and Privacy 2015
DOI: 10.1109/sp.2015.53
|View full text |Cite
|
Sign up to set email alerts
|

Missing the Point(er): On the Effectiveness of Code Pointer Integrity

Abstract: Abstract-Memory corruption attacks continue to be a major vector of attack for compromising modern systems. Numerous defenses have been proposed against memory corruption attacks, but they all have their limitations and weaknesses. Stronger defenses such as complete memory safety for legacy languages (C/C++) incur a large overhead, while weaker ones such as practical control flow integrity have been shown to be ineffective. A recent technique called code pointer integrity (CPI) promises to balance security and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 39 publications
1
88
0
Order By: Relevance
“…Kuznetsov et al [39] implement CPI by placing all code pointers in a secure region which (in 64-bit mode) is hidden by randomizing its offset in the virtual address space. However, Evans et al [23] successfully bypass this CPI implementation using side-channel attacks enabled by the large size of the secure region.…”
Section: Introductionmentioning
confidence: 99%
“…Kuznetsov et al [39] implement CPI by placing all code pointers in a secure region which (in 64-bit mode) is hidden by randomizing its offset in the virtual address space. However, Evans et al [23] successfully bypass this CPI implementation using side-channel attacks enabled by the large size of the secure region.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we used a randomization-based approach to protect the stack. However, all randomization-based approaches must face two major threats: lack of entropy and information disclosure [26]. We address the entropy problem by mapping kernel stack to a unused VA above the logical map (top 256GB).…”
Section: Kernel Stack Randomizationmentioning
confidence: 99%
“…Researchers have shown that brute-force attacks can bypass diversity, especially in services that automatically restart without rerandomization after crashing [6,15,33,34]. We use software booby traps to counter this threat [10].…”
Section: Countering Guessing Attacksmentioning
confidence: 99%
“…However, on x86-64 where segmentation is not fully available, CPI protects the safe region though information hiding or software-fault isolation. Evans et al [15] recently demonstrated a weakness in one of the x86-64 CPI implementations that can be leveraged to locate and compromise the safe region.…”
Section: Control-flow Integritymentioning
confidence: 99%